Comparison of Subcutaneous Infiltration With Intraperitoneal Instillation of Bupivacaine in Reduction of Early Postoperative Pain After Laparoscopic Cholecystectomy - Kamal, Muhammad Aizaz; Khan, Waseem Yar; Arooj, Sana; Khan, Muhammad Yaseen; Imran, Muhammad; Qazi, Shafia (Biological and Clinical Sciences Research Journal, 2025)
Postoperative pain remains a significant concern following laparoscopic cholecystectomy. Bupivacaine, a long-acting local anesthetic, is commonly used through different administration routes to reduce early postoperative pain. Determining the most effective delivery method may enhance recovery and improve patient comfort. Objective: To compare the effectiveness of subcutaneous infiltration versus intraperitoneal instillation of bupivacaine in reducing early postoperative pain following laparoscopic cholecystectomy. Methods: A quasi-experimental study was conducted at the Department of General Surgery, Qazi Hussain Ahmad Medical Complex, Nowshera, from December 2022 to June 2023. Sixty-two patients meeting the inclusion criteria were randomly assigned to two equal groups. Group A received 20 ml of 0.25% bupivacaine via subcutaneous infiltration at port sites, while Group B received the same dose intraperitoneally before the completion of the procedure. Pain intensity was assessed at 1, 4, 8, 12, and 24 hours postoperatively using the Visual Analogue Scale (VAS). Data were analyzed using SPSS Version 25, with p-values ≤0.05 considered statistically significant. Results: The mean age of participants was 45.92 ± 8.73 years. Gender distribution included 30 (51.6%) males and 32 (48.4%) females. No significant differences in age (p = 0.31) or gender (p = 0.22) were observed between groups. At 1 hour postoperatively, Group A had a higher mean VAS score (7.45 ± 0.89) compared to Group B (5.64 ± 0.84) (p = 0.00). At 24 hours, pain scores remained significantly lower in Group B (1.65 ± 0.61) compared to Group A (2.29 ± 0.86) (p = 0.00). Conclusion: Both subcutaneous infiltration and intraperitoneal instillation of bupivacaine effectively reduce early postoperative pain following laparoscopic cholecystectomy. However, intraperitoneal instillation provides significantly superior pain control at both early and later postoperative periods.